Camtasia Studio: Software Multimedia dalam Pembelajaran Menyimak Arab di Era Industri 4.0 - Toifah, Nur (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
A teacher is the spearhead of education, he must be able to revolutionize the teaching process properly, namely by changing the curriculum, strategies, materials, evaluation, and learning media that are in accordance with the demands of the 4.0 industrial revolution. This is the responsibility of all teachers, including Arabic teachers in Arabic listening skills in ST class. 12, Special Program for Arabic Language Development at State Islamic University of Maulana Malik Ibrahim Malang which uses Camtasia studio software in Arabic listening learning. The method of this research is descriptive qualitative. This media is useful for students in the form of increasing their learning motivation, changing behavior, providing new motivation and refreshment, providing meaningful lessons, expanding experiences and insights, and achieving the learning objectives of Arabic listening, as well as preparing them to face the era of the industrial revolution 4.0. The result of this research is that learning Arabic listening with Camtasia studio software media has three stages, namely the preliminary stage, which includes orientation, apperception, motivation, giving references, second: the core stage of learning, which includes observing, exploring, associating, communicating, and third: the closing stage, which includes conclusions, reflection and evaluation, motivation, and also prayers and greatings.